2003
DOI: 10.1046/j.1365-2699.2003.00956.x
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity and biogeography of the islands of the Kuril Archipelago

Abstract: Aim Based on seven consecutive seasons of biotic survey and inventory of the terrestrial and freshwater plants and animals of the 30 major islands of the Kuril Archipelago, a description of the biodiversity and an analysis of the biogeography of this previously little known part of the world are provided.Location The Kuril Archipelago, a natural laboratory for investigations into the origin, subsequent evolution, and long-term maintenance of insular populations, forms the eastern boundary of the Okhotsk Sea, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 13 publications
1
49
0
Order By: Relevance
“…This coeffi cient has frequently been used in island biogeographic analysis (e.g. How and Kitchener 1997;Hice and Schmidly 2002;Pietsch et al 2003). The resultant association matrix was clustered using the unweighted pair group method with arithmetic mean (UPGMA).…”
Section: Discussionmentioning
confidence: 99%
“…This coeffi cient has frequently been used in island biogeographic analysis (e.g. How and Kitchener 1997;Hice and Schmidly 2002;Pietsch et al 2003). The resultant association matrix was clustered using the unweighted pair group method with arithmetic mean (UPGMA).…”
Section: Discussionmentioning
confidence: 99%
“…The Bussol Strait is the widest strait in the Kuril Island chain, 109 km wide from Urup Island to Simushir Island (30 km between Urup and Chirpoi, and 79 km between Chirpoi and Simushir). The strait has a strong current flowing between the Pacific Ocean and the Sea of Okhotsk, and it is recognized as a biogeographic barrier to the movement of plants and animals from Hokkaido to the central and northern islands (Pietsch et al, 2003). Only three of the 49 pieces of obsidian from Hokkaido sources in this study were found north of the strait, one piece of obsidian from the Shirataki-A source on Chipoi Island, and one piece each from the Shirataki-A and Oketo-1 sources on Shiashkotan Island.…”
Section: Discussionmentioning
confidence: 99%
“…The total number of insects for Mauritius is likely to be an underestimate given that many taxa are taxonomically understudied. Compared to Hawaii (Miller and Elredge 1996), the island has a less diverse fauna but compared to Henderson Island (Benton 1995) and Kuril islands (Pietsch et al 2003), the fauna is more diverse. However, the evidence obtained from the data cannot be directly compared since the islands are from geographically different regions and vary in terms of size and degree of isolation.…”
Section: The Native Insect Faunamentioning
confidence: 97%
“…Basset et al 2000;Chung et al 2000) as well as on smaller remote islands (e.g. Pietsch et al 2003;Miller and Elredge 1996;Benton 1995). Such studies, as well as providing a better understanding of the native arthropod fauna, can enhance the conservation value of these regions.…”
Section: Introductionmentioning
confidence: 99%